The cAMP/PKA Pathway Inhibits Beta-amyloid Peptide Release from Human Platelets. (15th January 2019) - Sepúlveda, C.; Hernández, B.; Burgos, C.F.; Fuentes, E.; Palomo, I.; Alarcón, M.
Highlights: The Alzheimer Disease is the most common cause of senile dementia in mid to late-life. Cerebral amyloid angiopathy is correct because is a Disease. The platelets were inhibited by forskolin a reduction in the processing of the APP. The platelets were inhibited by forskolin a reduction in the processing of the Aβ peptide. Abstract: The main component of Alzheimer's disease (AD) is the amyloid-beta peptide (Aβ), the brain of these patients is characterized by deposits in the parenchyma and cerebral blood vessels known as cerebral amyloid angiopathy (CAA). On the other hand, the platelets are the major source of the Aβ peptide in circulation and once secreted can activate the platelets and endothelial cells producing the secretion of several inflammatory mediators that finally end up unchaining the CAA and later AD. In the present study we demonstrate that cAMP/PKA pathway plays key roles in the regulation of calpain activation and secretion of Aβ in human platelets. We confirmed that inhibition of platelet functionality occurred when platelets were incubated with forskolin (molecule that rapidly increased cAMP levels). In this sense we found that platelets pre-incubated with forskolin (20 μM) present a complete inhibition of calpain activity and this effect is reversed using an inhibitor of protein kinase A. Consequentially, when platelets were inhibited by forskolin a reduction in the processing of the APP with the consequent decrease in the Aβ peptide secretion was observed. Therefore our study provides novel insight in relation to the mechanism of processing and release of the Aβ peptide from human platelets.